Dataset Orbitrap Raw-Data Stress Hypothalamus(1h-24h) - Infantes-López, M. Inmaculada; Nieto-Quero, Andrea; Pérez-Martín, Margarita; Pedraza-Benítez, María del Carmen (Universidad de Málaga, 2023)
We have examined the effect of an acute stress in the proteomic profile of hypothalamus. For this purpose, to extract information from proteomic profiles (1 and 24 hours post-acute stress) a Quadrupole-Orbitrap mass spectrometry (Q-Orbitrap-MS) was used for the massive identification and quantification of hypothalamic proteins. After collecting the raw data extracted from this technique, for each proteomic profile, a functional enrichment study was performed. Firstly, the significantly overexpressed and underexpressed hypothalamic proteins of the right hemisphere of experimental groups with their respective controls (stress/control) were selected. Then, using STRING, the number of interactors was increased to 100 for both over- and under-expressed proteins. Furthermore, MCODE was used as a clustering tool for the protein‒protein interaction network obtained from STRING. After that, a functional enrichment analysis was performed using DAVID by introducing each protein gene name grouped into the clusters from the previous step. Biological processes in each protein clustering were determined as well as the function it is involved in. Finally, a network analysis of the GO terms obtained from DAVID was performed so that it was easier to interpret and integrate the biological implications of the results. Data were validate by using a western blot analysis. In the end, the main conclusion was that this short-term stressor altered the protein profile of the hypothalamus, changing the protein abundance after 1 hour or 24 hours of stress application.
Keywords: Estrés (Psicología); Hipotálamo; Acute stress; Proteomic profile; Hypothalamus